2014
DOI: 10.1073/pnas.1323628111
|View full text |Cite
|
Sign up to set email alerts
|

Representations of space, time, and number in neonates

Abstract: A rich concept of magnitude-in its numerical, spatial, and temporal forms-is a central foundation of mathematics, science, and technology, but the origins and developmental relations among the abstract concepts of number, space, and time are debated. Are the representations of these dimensions and their links tuned by extensive experience, or are they readily available from birth? Here, we show that, at the beginning of postnatal life, 0-to 3-dold neonates reacted to a simultaneous increase (or decrease) in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
199
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(216 citation statements)
references
References 37 publications
14
199
3
Order By: Relevance
“…Research measuring looking-time in infants has shown that in the first year of life infants are already sensitive to congruent pairings of number and physical size (de Hevia et al, 2014;de Hevia & Spelke, 2010;Lourenco & Longo, 2010) but do not recognize congruency for pairings of number and luminance (de Hevia & Spelke, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research measuring looking-time in infants has shown that in the first year of life infants are already sensitive to congruent pairings of number and physical size (de Hevia et al, 2014;de Hevia & Spelke, 2010;Lourenco & Longo, 2010) but do not recognize congruency for pairings of number and luminance (de Hevia & Spelke, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that infants are sensitive to the relational congruence between large numerosities, large objects, and long durations in comparison to small numerosities, small objects, and short durations. Furthermore, these associations have recently been found in neonates just hours after birth (de Hevia, Izard, Coubart, Spelke, & Streri, 2014), suggesting that they are present even before infants have had a chance to experience correlations between these dimensions in the external world.…”
mentioning
confidence: 94%
“…Note that we do not discuss here how younger infants temporally locate events. Very young infants are sensitive to some temporal features of stimuli such as duration and rhythm, and this extends even to neonates (de Hevia et al, 2014;Nazzi et al, 1998), but it is extremely difficult to examine how they locate events in time.…”
Section: A Developmental Model Of the Acquisition Of Temporal Conceptsmentioning
confidence: 99%
“…For instance, at birth humans expect that an increase (or decrease) in number is accompanied by an equivalent increase (or decrease) in object's size [1]. In adults, comparative judgements on number or on objects' size show reciprocal influences [2].…”
Section: Introductionmentioning
confidence: 99%